2002
DOI: 10.1038/sj.onc.1205220
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the FUS domain restores liposarcoma development in CHOP transgenic mice

Abstract: Fusion proteins created by chromosomal abnormalities are key components of mesenchymal cancer development. The most common chromosomal translocation in liposarcomas, t(12;16)(q13;p11), creates the FUS ± CHOP fusion gene. In the past, we generated FUS ± CHOP and CHOP transgenic mice and have shown that while FUS ± CHOP transgenic develop liposarcomas, mice expressing CHOP, which lacks the FUS domain, display essentially normal white adipose tissue (WAT) development, suggesting that the FUS domain of FUS ± CHOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
3
17
0
1
Order By: Relevance
“…White adipose tissue from Ef1a-FUS or Ef1a-CHOP single transgenic mice was normal. Creation of double transgenic Ef1a-FUS ϫ Ef1a-CHOP mice resulted in liposarcomas that develop at the same rate as the FUS-CHOP fusion gene mice (Perez-Mancera et al, 2002). Tumors were not identified in any other tissues, despite the ubiquitous expression from the Ef1a promoter.…”
Section: Myxoid Liposarcomamentioning
confidence: 91%
See 1 more Smart Citation
“…White adipose tissue from Ef1a-FUS or Ef1a-CHOP single transgenic mice was normal. Creation of double transgenic Ef1a-FUS ϫ Ef1a-CHOP mice resulted in liposarcomas that develop at the same rate as the FUS-CHOP fusion gene mice (Perez-Mancera et al, 2002). Tumors were not identified in any other tissues, despite the ubiquitous expression from the Ef1a promoter.…”
Section: Myxoid Liposarcomamentioning
confidence: 91%
“…To determine the protein domain that is sufficient for tumorigenesis, the FUS and CHOP genes were examined in separate mouse models (Perez-Mancera et al, 2002). White adipose tissue from Ef1a-FUS or Ef1a-CHOP single transgenic mice was normal.…”
Section: Myxoid Liposarcomamentioning
confidence: 99%
“…No studies have analyzed FUS expression in human cancers, including GC. However, it has been shown that expression of the FUS domain restores liposarcoma development in CHOP-transgenic mice (40), suggesting that gain-offunction mutation of both FUS and CHOP is important. In the present study, FUS was a candidate marker for tumor progression, and we showed that a high level of FUS expression was associated with advanced N grade and stage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, transgenic mice expressing FUS-CHOP or CHOP-FUS transgenes under the control of the ubiquitous E1Fa promoter gave rise to similar liposarcomas that resemble their human counterparts [66,67]. On the other hand, although the uncontrolled expression of CHOP after the chromosomal translocation seems to play a leading role in liposarcoma development [64], transgenic mice expressing CHOP alone do not develop any tumor [67] and the expression of FUS restores liposarcoma development in these CHOP-transgenic mice [68]. These results provide evidence that the FUS portion of FUS-CHOP also plays a specific and critical role in the pathogenesis of liposarcoma.…”
Section: Human Mscsmentioning
confidence: 99%